Canine atopic dermatitis (atopy) - SARIDOMICHELAKIS (Μ. Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ), M. N.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F. (Journal of the Hellenic Veterinary Medical Society, 2018)
Canine atopic dermatitis is a common clinical entity, characterized by pruritus due to sensitization against common enviromental allergens. It has been proven that there is strong breed predisposition. Genetically programmed dogs overproduct reaginic antibodies (IgE and/or IgGd) after their exposure to airborne allergens (dust mites, epithelia, pollens and molds) which consequently fix themselves to the mast cells of the skin. After reexposure to the same allergens these cells degranulate, with subsequent release of many pharmacologically active substances (histamine, leucotrienes, Prostaglandines etc). However, this is a rather simplistic explanation; the true pathogenesis of atopy is more complicated and still not well understood. Clinical signs first appear between 6 months and 3 years of age. Pruritus, the mainstay of atopy, can be seasonal or perennial. Skin lesions, appearing in later, are attributed to pruritus and/or to secondary complications (staphylococcal pyoderma, seborrhea, dry skin, Malassezia dermatitis). The diagnosis, based on history and clinical findings, necessitates exclusion of other pruritic skin diseases and identification of the offending allergens by using the intradermal test and/or serology (ELISA, RAST). The latter method is diagnostically inferior to intradermal skin test due to the high rate of false positive reactions. Therapeutic options include avoidance of the allergens responsible for sensitization, systemic therapy with glucocorticoids, antihistamines and essential fatty acids in various combinations, topical antipruritic therapy, hyposensitization which is the best therapeutical modality for the perennial form of the disease and management of secondary complications as well as of other concurrent allergic skin diseases, such as food and flea allergy.